Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
Bài giải
a, \(-2\left(2x-8\right)+3\left(4-2x\right)=-72-5\left(3x-7\right)\)
\(-4x+8+12-6x=-72-15x+7\)
\(-10x+20=-65-15x\)
\(-10x+15x=-65-20\)
\(5x=-85\)
\(x=-85\text{ : }5\)
\(x=-17\)
b, \(3\left|2x^2-7\right|=33\)
\(\left|2x^2-7\right|=33\text{ : }3\)
\(\left|2x^2-7\right|=11\)
\(\Rightarrow\orbr{\begin{cases}2x^2-7=-11\\2x^2-7=11\end{cases}}\Rightarrow\orbr{\begin{cases}2x^2=-4\text{ ( loại ) }\\2x^2=18\end{cases}}\Rightarrow\text{ }x^2=9\text{ }\Rightarrow\text{ }x=\pm3\)
\(\Rightarrow\text{ }x=\pm3\)
bài 1
a) \(15+\left(32-2x\right)=65\)
\(32-2x=65-15\)
\(32-2x=50\)
\(2x=32-50\)
\(2x=-18\)
\(x=-18:2\)
\(x=-9\)
vậy \(x=-9\)
b)\(18.\left(x-5\right)^2=72\)
\(\left(x-5\right)^2=72:18\)
\(\left(x-5\right)^2=4=2^2\)
\(x-5=2\)
\(x=2+5=7\)
vậy \(x=7\)
c)\(\left|19-x\right|-6=0\)
\(\left|19-x\right|=0+6=6\)
\(19-x=\pm6\)
\(\left[{}\begin{matrix}19-x=6\\19-x=-6\end{matrix}\right.\Rightarrow\left[{}\begin{matrix}x=13\\x=25\end{matrix}\right.\)
vậy \(x\in\left\{13;25\right\}\)
a/ \(27^{11}=\left(3^3\right)^{11}=3^{33}\); \(81^8=\left(3^4\right)^8=3^{32}< 3^{33}\Rightarrow81^8< 27^{11}\)
b/ \(3^{2n}=\left(3^2\right)^n=9^n\); \(2^{3n}=\left(2^3\right)^n=8^n< 9^n\Rightarrow2^{3n}< 3^{2n}\)
a. 2711= (33)11 = 333
818 = (34)8 = 332
Suy ra 333>332 hay 2711>818
b. 32n = (32)n = 9n
23n = (23)n = 8n
Mà 9>8 suy ra 9n>8n hay 32n>23n
c. 523 = 522 . 5
(6.5)22 = 622 . 522
Vì 622>5 suy ra 522 . 5<622 . 522 hay 523<(6.5)22
d. 7245-7244 = 7244(72-1) = 7244 . 71
7244-7243 = 7243(72-1) = 7243 . 71
Vì 7244>7243 suy ra 7244 . 71>7243 . 71 hay 7245-7244>7244-7243
Ta có:
7245 - 7244 = 7244.(72 - 1) = 7244.71
7244 - 7243 = 7243.(72 - 1) = 7243.71
Vì 7244.71 > 7243.71
=> 7245 - 7244 > 7244 - 7243
Ta có:
\(72^{45}-72^{44}=72^{44}\left(72-1\right)=72^{44}.71\)
\(72^{44}-72^{43}=72^{43}\left(72-1\right)=72^{43}.71\)
Vì \(72^{44}.71>72^{43}.71\) nên \(72^{45}-72^{44}>72^{44}-72^{43}\)
So sánh : và \(72^{44}-72^{43}\)
Ta có :
\(72^{45}-72^{44}=72^{44}\left(72-1\right)\)
\(72^{44}-72^{43}=72^{43}\left(72-1\right)\)
Vì 7244 > 7243 => 7244 (72-1) > 7243 (72-1)
hay 7245 -7244 > 7244 - 7243
2x^2 -72 = 0
= 2x^2 = 0+72
= 2x^2 = 72
= x^2 = 72:2
= x^2 = 36
= x^2 = 6^2
= x = 6